GUIDELINES FOR IMPROVING THE QUALITY OF PUBLIC HIRE VEHICLE SERVICES IN HUA HIN DISTRICT, PRACHUAP KHIRI KHAN PROVINCE - Neamsin, Wanida; Chinnasri, Walaiporn (Journal of MCU Phetchaburi Review, 2025)
This research aimed to 1) Study the level of development of public transport service quality. 2) Compare opinions on the development of the quality of public transportation services classified by personal characteristics. 3) Study the factors in service that have a causal relationship with the quality of public transport service. 4) Guidelines for developing the quality of public transport service. The sample group consisted of 384 Thai people who use public transport services in Hua Hin District and 10 key informants. Data were analyzed using percentages, means, standard deviations, one-way variance, multiple regression, and content analysis. Findings: 1) the development of public transportation service quality is at a high level. 2) People with different ages, education levels, occupations, and average monthly incomes have different opinions on the quality of public transportation services. 3) Service factors, including price and service process, have a cause-and-effect relationship with public transportation service quality, with a statistical significance level of 0.001. Recipient perception is at a statistical significance level of 0.01, and recipient expectations are at a statistical significance level of 0.05. 4) Guidelines for improving the quality of public transportation services should include clear standards for staff training, vehicle safety, and transparency in information provision. These include a system for responding to and listening to passenger feedback quickly, promoting understanding of the needs of diverse customer groups, and building confidence through modern inspection measures and technology to increase satisfaction and trust, ensuring sustainable long-term service use.